2016
DOI: 10.1103/physrevc.94.044616
|View full text |Cite
|
Sign up to set email alerts
|

Examination of experimental conditions for the production of proton-rich and neutron-rich hypernuclei

Abstract: After the demonstration of the feasibility of hypernuclear spectroscopy with heavy-ion beams, the HypHI Collaboration will next focus on the study of proton-and neutron-rich hypernuclei. The use of a fragment separator for the production and separation of rare isotope beams is a crucial aspect to producing hypernuclei far from the stability line. Precise spectroscopy of exotic hypernuclei is planned to be carried out at the GSI and later at the FAIR facility with the FRS and Super-FRS fragment separators. A sy… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 30 publications
0
24
1
Order By: Relevance
“…The hypernuclear yields in the present work are smaller than those in Ref. [26], and the form of Z-N plane population is different. The differences are due to that in Ref.…”
Section: Model Descriptioncontrasting
confidence: 91%
See 1 more Smart Citation
“…The hypernuclear yields in the present work are smaller than those in Ref. [26], and the form of Z-N plane population is different. The differences are due to that in Ref.…”
Section: Model Descriptioncontrasting
confidence: 91%
“…The differences are due to that in Ref. [26] the geometrical cross sections instead of the inelastic cross sections were wrongly taken to estimate the hypernuclear yields, and breakup of the hot primary hyperresidues was not considered [49]. Actually, the production cross sections are quite sensitive to the adopted excitation energies, since the breakup probability is proportional to (E x −U ) 3n/2−5/2 , where U is the Coulomb barrier and n is the number of cold residues after breakup [46].…”
Section: Model Descriptionmentioning
confidence: 80%
“…The measured mean life was found to be 86 +33 −26 ps, which is two to three times shorter than lifetimes measured in this hypernuclear mass range in more recent, better controlled (π + , K + ) experiments at KEK (Bhang et al, 1998;Park et al, 2000), as demonstrated in Table VI. More recently, the HypHI Collaboration at GSI reported lifetimes of 3 Λ H and 4 Λ H produced by bombarding a carbon target with a 2 GeV/nucleon 6 Li beam (Rappold et al, 2013a). The lifetime of 3 Λ H has also been measured in heavy-ion central collisions, by the STAR Collaboration at the BNL-RHIC collider (Abelev et al, 2010) and by the ALICE Collaboration at CERN-LHC (Adam et al, 2016a).…”
Section: Hypernuclear Lifetime Measurementsmentioning
confidence: 99%
“…Various aspects of hypernuclear production in heavy-ion collisions were considered in many works, see [26][27][28]. Estimates [27] show that observation not only single-Λ, but also double-Λ hypernuclei including 5 ΛΛ H and 5 ΛΛ He at the NICA complex is quite feasible.…”
Section: Double-strangeness Hypernucleimentioning
confidence: 99%